Fractal characterisation of surface profile and optimisation in EDM using Taguchi method. (24th July 2009) - Sahoo, P.; Barman, T.K.; Routara, B.C.
This paper presents an experimental study of fractal characteristics of surface profile produced in Electrical Discharge Machining (EDM) and optimisation of machining parameters based on L27 Taguchi orthogonal design for tungsten carbide, mild steel and brass. Pulse current has the most significant influence in controlling fractal dimension characteristics for all the three materials. Pulse-off time has some influence in case of mild steel while pulse-on time has some influence in case of tungsten carbide. The interactions between the machining parameters also influence the fractal dimension. Optimum machining parameter combinations are identified to yield optimum (maximum) fractal dimension by Taguchi analysis.